Efficient in vitro embryo production using in vivo-matured oocytes from superstimulated Japanese Black cows - Junki EGASHIRA; Yusuke IHARA; Hafiza KHATUN; Yasuhiko WADA; Toshihiro KONNO; Hideki TATEMOTO; Ken-ichi YAMANAKA (The Society for Reproduction and Development, 2019)
We examined whether the use of in vivo-matured oocytes, collected by ovum pick-up (OPU) from superstimulated Japanese Black cows, can improve the productivity and quality of in vitro produced embryos. The cows were superstimulated by treatment with progesterone, GnRH, FSH and prostaglandin F2α according to a standardized protocol. The resulting in vivo-matured oocytes were collected by OPU and used subsequently for the other experiments. The immature oocytes from cows in the non-stimulated group were collected by OPU and then subjected to maturation in vitro. We found that the rate of normally distributed cortical granules of the matured oocyte cytoplasm in the superstimulated group was significantly higher than that in the non-stimulated group. The normal cleavage rate (i.e., production of embryos with two equal blastomeres without fragmentation) and freezable blastocyst rate were significantly higher in the superstimulated group than in the non-stimulated group. Among the transferable blastocysts, the ratio of embryos from normal cleavage was also significantly higher in the superstimulated group than in the non-stimulated group. For in vivo-matured oocytes, it was observed that the pregnancy rates were significantly higher when normally cleaved embryos were used for transfer. Taken together, these results suggest that high-quality embryos with respect to developmental kinetics can be efficiently produced with the use of in vivo-matured oocytes collected by OPU from superstimulated Japanese Black cows.